Clinical Efficacy of Conventional and Diode Laser-Assisted Frenectomy in Patients with Different Abnormal Frenulum Insertions: A Retrospective Study - ÖZTÜRK ÖZENER, HAFİZE; KURU, LEYLA (MARY ANN LIEBERT, INC, 2020)
Objective:This retrospective study aimed to assess the recurrence of frenulum attachment and clinical parameters following conventional and diode laser-assisted frenectomy in patients with abnormal frenulum insertions. Material and methods:The records of 429 patients who underwent maxillary labial frenectomy between 2016 and 2018 were screened. A total of 70 records were included and evaluated based on gender, age, frenulum type, presence of diastema, periodontal disease, and surgical technique. Plaque index (PI), gingival index (GI), and probing depth (PD) were evaluated at baseline and 6 weeks postoperatively. Recurrence was determined by assessing the alteration in the distance from the frenulum attachment to the mucogingival junction (FMGJ) at baseline, 6 weeks, and 12 months. Results:Out of 70 patients (female/male 47/23; age 35.24 +/- 11.69 years), 32.9% presented gingival, 38.6% papillary, and 28.6% papilla-penetrating frenulum attachments. Clinical parameters and mean FMGJ values between the conventional (n = 36) and diode laser (n = 34) groups demonstrated no differences at baseline (p > 0.05). PI and GI were significantly higher in the conventional group (p < 0.001), whereas PD was similar (p > 0.05) at 6 weeks. No recurrence was observed in any of the patients at the sixth week. Moreover, 31 participants in the conventional group and 33 participants in the diode-laser group, a total of 64 patients (91.43%), did not present recurrence after 12 months. Conclusions:Within the limits of the study, considering the absence of recurrence in all types of abnormal frenulum insertions in both treatment groups, it was concluded that the diode laser could be used effectively as an alternative to the conventional frenectomy technique.
Keywords: labial frenulum; laser therapy; oral hygiene; recurrence; PERCEPTIONS; CO2-LASER